2021
DOI: 10.1038/s41419-021-04377-1
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of hepatic stellate cell activation extends into chronic liver disease

Abstract: Activated hepatic stellate cells (aHSC) are the main source of extra cellular matrix in liver fibrosis. Activation is classically divided in two phases: initiation and perpetuation. Currently, HSC-based therapeutic candidates largely focus on targeting the aHSCs in the perpetuation phase. However, the importance of HSC initiation during chronic liver disease (CLD) remains unclear. Here, we identified transcriptional programs of initiating and activated HSCs by RNA sequencing, using in vitro and in vivo mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…PCA plot shows a division of CTR and VPA treated slices over PC1, which accounts for 34% of variance ( Figure 2F ). Moreover, the fibrogenic aHSC gene signature recently identified by De Smet et al ( 9 ), is significantly enriched in standard PCLS culture conditions when compared to VPA supplemented conditions ( Figure 2G ). Differential gene expression analysis showed that 48 genes were differentially upregulated and 130 genes were differentially downregulated (such as Aebp1, Col1a1 , and Col3a1) in the presence of VPA compared to control conditions (data not shown).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…PCA plot shows a division of CTR and VPA treated slices over PC1, which accounts for 34% of variance ( Figure 2F ). Moreover, the fibrogenic aHSC gene signature recently identified by De Smet et al ( 9 ), is significantly enriched in standard PCLS culture conditions when compared to VPA supplemented conditions ( Figure 2G ). Differential gene expression analysis showed that 48 genes were differentially upregulated and 130 genes were differentially downregulated (such as Aebp1, Col1a1 , and Col3a1) in the presence of VPA compared to control conditions (data not shown).…”
Section: Resultsmentioning
confidence: 61%
“…Traditionally, in vitro models of liver fibrosis rely on 2D cultures of primary HSCs. However, while these in vitro activated HSCs partly resemble their in vivo counterpart, they do not fully recapitulate in vivo HSC activation ( 7 9 ). The possible reason for this discrepancy is the loss of micro-environmental context in these 2D cultures.…”
Section: Introductionmentioning
confidence: 84%
“…The varied molar mass entails altering the copolymer composition as the DP value of the PNonOx segments was kept constant while the DP value of the PEtOx segments changed. This was evident from characterization data obtained by 1 H NMR spectroscopy (Figures 3 and S8). The spectra revealed signals ascribed to the PNonOx (capital letters "A− E") as well as the PEtOx (small letters "a−c") segments, which were partially overlapping with each other.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…It is characterized by cell death, immune cell activation, and the increased production and deposition of collagen from activated hepatic stellate cells (HSCs). The activation and collagen production by stellate cells is a hallmark and driving force for the liver fibrotization that results in liver cirrhosis . Thus, interfering with HSC activation and collagen production represents a promising avenue to treat chronic liver diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation